2015
DOI: 10.1080/15476278.2015.1055431
|View full text |Cite
|
Sign up to set email alerts
|

Meckel Gruber syndrome, A case report

Abstract: ABSTRACT. Introduction: Meckel-Gruber Syndrome was first described by J R Meckel in 1822. It is an autosomal recessive disorder, and is caused by the failure of mesodermal induction. The typical triad of Meckel-Gruber Syndrome (MGS) involves meningo-encephalocele, polycystic kidneys and postaxial polydactyly. The worldwide incidence varies from 1 in 1.300 to 1 in 140.000 live births.Case: In this report, we present a case of MGS in which the diagnosis was made at 19 weeks of gestation based on ultrasonographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…At 10-14 weeks of gestation, USG is usually successful in detecting the triad of polycystic kidneys, polydactyly, and occipital encephalocele [11][12][13]. Two characteristics of the triad would strongly suggest the diagnosis of MKS [14,15]. Surprisingly, USG was inconclusive before the 7th month of gestation at 3 different pregnancies in our case.…”
Section: Discussionmentioning
confidence: 58%
“…At 10-14 weeks of gestation, USG is usually successful in detecting the triad of polycystic kidneys, polydactyly, and occipital encephalocele [11][12][13]. Two characteristics of the triad would strongly suggest the diagnosis of MKS [14,15]. Surprisingly, USG was inconclusive before the 7th month of gestation at 3 different pregnancies in our case.…”
Section: Discussionmentioning
confidence: 58%
“…A variety of other malformations have been reported in MGS. MGS may be associated with agenesis of cerebellar vermis and posterior fossa cyst suggestive of DWM, cystic hygroma, cardiac malformation, microcephaly, IUGR, and cleft palate (9,(11)(12)(13). Hepatic fibrosis and bile duct proliferation has also been reported and can be present in up to 1/5th of the cases (4,14).…”
Section: Discussionmentioning
confidence: 99%
“…The prevelance varies from 1 per 1300 to 1 per 140000 live births [1]. The highest incidence was reported in Gujarati Indians 1 per 1300 [3] and Finland9000 [4]. A population based study of Meckel-Gruber syndrome in Europe from 1990 to 2011 reported a mean prevalence of 2.6 per 100 000 births and did not report any cases in Croatia [5].…”
Section: Dear Editormentioning
confidence: 97%